Effects of Breadfruit Leaf Extract in Reducing the Risk of Coronary Heart Disease - Laurencia Alimin; Angwen Rial Huga; Brigitta Olivia (Indonesian Journal of Global Health Research, 2020)
Coronary heart disease (CHD) is the number one cause of death globally, caused by accumulation of plaque, a mixture of fat, cholesterol, and calcium deposits in the arteries for years which over time causes narrowing and hardening of the coronary arteries so that oxygen supply in the blood decreases. CHD can bepotentiallyprevented with active substancescontained by plants such as breadfruit.Breadfruit leaf(Artocarpus altilis) is one of the natural ingredients that contain flavonoids, which can reduce cholesterol, triglycerides and LDL in the blood so the risk of CHD will decrease.Objectiveto describe the potential anticholesterol effects of breadfruit in coronary heart diseasecaused by high cholesterol. This paper used literature study involving 16 libraries both nationaland international books and journal.Conclusions: Breadfruit leaf has the effect of preventing the risk of coronary heart disease by lowering cholesterol, triglyceride and LDL levels in the blood without side effects. Keywords: breadfruit leaf, flavonoid, coronary heart disease